Yoga during Pregnancy: A Review - Babbar, Shilpa; Parks-Savage, Agatha C.; Chauhan, Suneet P. (American Journal of Perinatology, 2012)
The purpose of this review article is to evaluate the peripartum outcomes of yoga during pregnancy, including the postpartum period and lactation. The PubMed database was analyzed from January 1970 to January 2011. We identified five prospective observational studies (n = 575) and three randomized clinical trials (RCTs; n = 298), which were analyzed separately. The nonrandomized trials indicated a significant reduction in rates of preterm labor (p < 0.0006), intrauterine growth retardation (p <0.003), low birth weight (p < 0.01), pregnancy discomforts (p = 0.01), and perceived sleep disturbances (p = 0.03) in those who practiced yoga during pregnancy. Results of the RCTs indicated that doing yoga during pregnancy can significantly lower pain and discomfort (p < 0.05) and perceived stress (p = 0.001) and improve quality of life in physical domains (p = 0.001). All three RCTs were poorly compliant with the Consolidated Standard of Reporting Trials statement. While awaiting an appropriately designed RCT to determine the benefits of yoga during pregnancy, it remains a viable exercise option.
Keywords: yoga; pregnancy; exercise; prenatal